Molecular Docking Analysis of Bioactive Compounds from Jatropha Curcas L. Leaves as Lipoxygenase Inhibitors and Antioxidant Candidates - Fahmi Sadik; Wa Ode Rufiyani; Muhammad Fakhrur Rajih Hi. Yusuf (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Oxidative stress results from an imbalance between reactive oxygen species (ROS) and the body's antioxidant defense system, contributing to various degenerative diseases. The enzyme Lipoxygenase (LOX) plays a crucial role in ROS formation; thus, its inhibition offers a strategic approach to mitigate oxidative damage. This study aims to evaluate the potential of bioactive compounds from Jatropha curcas L. leaves as LOX inhibitors using in silico approaches. The target protein (Human 15-LOX, PDB ID: 7LAF) and ligand structures were retrieved from the Protein Data Bank and PubChem. Flexible molecular docking simulations were performed using YASARA Structure to accommodate receptor side-chain adjustments, validated against the native ligand (XRP) and a positive control (Zileuton). The results revealed that Naringenin-7-O-β-D-glucopyranoside exhibited the strongest binding affinity (–10.41 kcal/mol), surpassing both the native ligand (–9.03 kcal/mol) and Zileuton (–7.48 kcal/mol), driven by extensive hydrogen bond networks with residues ASN173 and ASP625. Meanwhile, the aglycone (-)-Pinoresinol demonstrated competitive affinity (–8.80 kcal/mol) stabilized by hydrophobic interactions with PHE88 and TRP109. While glycosides showed superior potency, (-)-Pinoresinol and Epicatechin were identified as the most rational oral drug candidates, fulfilling Lipinski’s Rule of Five and demonstrating high intestinal absorption (>90%) in ADMET analysis. These findings provide a structure-based rationale for selecting J. curcas metabolites as promising LOX inhibitor candidates for further in vitro validation.